Pearson discover history student book 2 - Addison, Penny; Betridge, Sharon (Pakistan : Pearson (Kifayat Publishers), 2024)
Pearson Discover History 2 builds on the foundations of the first book, guiding students through more complex historical events, cultures, and themes. Using engaging stories, maps, images, and activities, it deepens understanding of ancient and medieval civilizations, key historical figures, and significant changes over time. The book fosters analytical thinking, historical inquiry, and a broader appreciation of the world$1 (Bs past.s
Keywords: History - Text Book